IMPLEMENTASI LAYANAN KONSELING KELOMPOK MENGGUNAKAN TEKNIK CLIENT-CENTERED THERAPY UNTUK MENGURANGI KEPRIBADIAN INTROVERT - Rehanaisha, Rehanaisha; Asrori, Muhammad; Yuline, Yuline (Universitas Tanjungpura, 2023)
This research aims to test the effectiveness of group counseling services using Client-Centered Therapy techniques to reduce introverted personalities in class VII students at SMP Negeri 22 Pontianak. The research method in this study uses a quantitative approach with a Quasi Experimental Design, using a One Group PreTest and Post-Test Design research design. The sampling technique in this research was the Purposive Sampling technique which resulted in five students. The data collection method used was an introvert personality questionnaire. And the data analysis technique in this research uses percentage analysis and T-Test for Paired Samples. The implementation of group counseling is carried out using four techniques from Client-Centered Therapy, namely Acceptance, Congruance, Understanding, and Nonjudgmental. The research results show that group counseling services using Client-Centered Therapy techniques are effective in reducing introverted personality, as evidenced by the results of the T-Test for Paired Samples with a value of t=-11.796 and a significance of 0.000 0.05 and the Effect Size calculation obtained a value of 9.848 1.00 which is included in the strong effect category (strong effect). So it was concluded that providing group counseling services using the Client-Centered Therapy technique provided very strong effectiveness in reducing introverted personalities in class VII students at SMP Negeri 22 Pontianak.